Porous Boron Nitride Materials: Influence of Structure, Chemistry and Stability on the Adsorption of Organics - Marchesini, Sofia; Wang, Xiyu; Petit, Camille (Frontiers in Chemistry, 2019)
Porous boron nitride (BN) is structurally analogous to activated carbon. This material is gaining increasing attention for its potential in a range of adsorption and chemical separation applications, with a number of recent proof-of-concept studies on the removal of organics from water. Today though, the properties of porous BN – i.e. surface area, pore network, chemistry – that dictate adsorption of specific organics remain vastly unknown. Yet, they will need to be optimized to realise the full potential of the material in the envisioned applications. Here, a selection of porous BN materials with varied pore structures and chemistries were studied for the adsorption of different organic molecules, either directly, through vapour sorption analyses or as part of a water/organic mixture in the liquid phase. These separations are relevant to the industrial and environmental sectors and are envisioned to take advantage of the hydrophobic character of the BN sheets. The materials were tested and regenerated and their physical and chemical features were characterized before and after testing. This study allowed identifying the adsorption mechanisms, assessing the performance of porous BN compared to benchmarks in the field and outlining ways to improve the adsorption performance further.